Studi Banding Pola Gerak Tari Kataga dengan Seni Gambar Cadas di Situs Tron Bon Lei, Alor, Nusa Tenggara Timur (Tinjauan Etno Arkeologi) - Antika, Tri; Mahirta (PURBAWIDYA, 2024)
The rock art of the Tron Bon Lei Site, Alor, East Nusa Tenggara has unique form because it is depicted in anthropomorphic figures. The figure is depicted in a certain movement pose and has attributes in the form of traditional clothing and weapons. Kataga dance is a traditional dance that was previously performed in death rituals after war in Sumba, East Nusa Tenggara. This article discusses the form of the anthropomorphic figures of the Tron Bon Lei Site Rock Art and the Kataga Traditional Dance forms with the aim of seeing the similarities and differences between the two objects in relation to the meaning of the rock art. This research was conducted using a qualitative method, namely a descriptive analytical approach. Data collection was carried out using field surveys and literature studies. The results of the research show that there are similarities between the rock art form and the Kataga Dance form. The similarities are in the movement poses, attributes and dance formations. It is hoped that this article can provide a new perspective in interpreting rock art, by looking at similar forms in contextual situation.